KONSTRUKSI SOSIAL MEDIA MASSA - Puji Santoso (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2016)
Reality is a social construct created by individuals. However, the truth of a social reality is relative, which applies appropriate specific context assessed by the relevant social actors. This scientific study was about to expose some analysis on the theory of social construction by humans subjectively through the mass media, as Berger and Luckman in the 1960s. Similarly, application of the theory presented in several studies done by some researchers. In this study note that media was very substance in the process of externalization, subjektivasi, and internalization in constructing social reality. The position of the social construction of the mass media is correct weaknesses and complement the social construction of reality, by putting all the advantages of mass media and the effects of media on the benefits of the social construction of the mass media on the social construction of reality.